Pixie pushes on - Bundy, Tamara (Nancy Paulsen Books, 2020)
Caring for a runt lamb helps Pixie gain empathy when, in the 1940s, her family moves to her grandparents' farm and her sister Charlotte contracts polio and is sent away.